A best practice model of open and distance learning (ODL) for studio-based architectural design courses / Abdul Hadi Nawawi ... [et al.] - Nawawi, Abdul Hadi; Rosman, Siti Hasniza; Ismail, Suhana; Zawawi, Emma Marinie; Ab Majid, Rohayu (UiTM Press, 2024)
In March 2020, distance education was enforced as a proactive procedure to control the spread of coronavirus. However, the COVID-19 circumstances provide evidence of the possibility of teaching architecture in other ways. This research explores various aspects that contribute to the success factors of ODL for studio-based architectural design courses which then forms the fundamentals to develop the best practice model of ODL for studio-based architectural design courses to improve the quality of teaching and learning process. This research used a quantitative design. Data was collected through surveys from thirty-four (34) respondents with expertise in conducting studio based architectural design courses to identify the success factors of ODL for the courses. Data was analysed using SmartPLS3 software for Partial Least Squares Structural Equation Modeling (PLS SEM) to assess the measurement and structural for reflective-formative model based on the significant value of the items studied. The results of the research revealed that the path coefficient analysis score of the teaching and learning approach is the highest, which is 0.892, while the design skills is 0.626. It has been shown that the relationship between indicators and constructs is highly correlated. This is then followed by the communication approach at -0.187, while the design-studio management strategies is -0.111, digital tools is 0.018 and comprehensive design is -0.007. The results also highlighted that the teaching and learning approach and design skills is the best practice for ODL. Overarchingly, this research provides insights into ODL in studio-based architectural design courses as a future direction in teaching architecture.